2000
DOI: 10.1098/rspb.2000.1041
|View full text |Cite
|
Sign up to set email alerts
|

A long photoperiod overrides non-photoperiodic factors in blue tits' timing of reproduction

Abstract: Endocrinological studies have contributed considerably to the development of theory concerning the proximate aspects of the timing of reproduction. In non-domesticated, avian species, the relative importance of the photoperiodic and non-photoperiodic factors in£uencing later stages of the breeding cycle, such as the onset of egg laying, remains unclear because egg laying is di¤cult to obtain with captive populations and laboratory experiments of breeding are rarely carried out in the framework of long-term ¢el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 28 publications
0
59
1
Order By: Relevance
“…Phenotypically plastic traits can obviously respond to more than one environmental variable, for example, seasonal timing of breeding in passerines depends on both ambient temperature and day length [41,42]. Assuming in our model that consumer phenology depends on more than one environmental variable would only make equation (2.5) more complex and hence lead to an even more restricted set of conditions that lead to no selection on consumer phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically plastic traits can obviously respond to more than one environmental variable, for example, seasonal timing of breeding in passerines depends on both ambient temperature and day length [41,42]. Assuming in our model that consumer phenology depends on more than one environmental variable would only make equation (2.5) more complex and hence lead to an even more restricted set of conditions that lead to no selection on consumer phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in these heterogeneous landscapes, where the different oak habitats are situated at similar altitude and exposed to similar ambient temperatures, the reproductive system of Blue Tits (e.g. see Caro et al 2006) does not seem to be sufficiently plastic to allow adaptive breeding time responses to very contrasting oak habitat types, most probably caused by maladapted photoperiodic responses in evergreen habitat (Lambrechts et al 1997b, Lambrechts & Perret 2000. However, the oak-caterpillar-tit ecosystem is known to be temperature-sensitive (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, proper choice of the relevant climatic parameters has to be inferred from a large number of possibilities, where a multitude of combinations are also possible. For example, it has frequently been shown that local temperatures are important for timing of breeding in birds (McCleery and Perrins 1998, Meijer et al 1999, Both et al 2004, Brommer et al 2005, but day length can also play a role (Lambrechts and Perret 2000). Ideally, therefore, several variables need to be explored simultaneously.…”
Section: Introductionmentioning
confidence: 99%